Northern Hemisphere interdecadal variability: A coupled air-sea mode - Timmermann, Axel; Latif, Mojib; Voss, R.; Grötzner, A. (Journal of Climate, 1998)
A coupled air–sea mode in the Northern Hemisphere with a period of about 35 years is described. The mode was derived from a multicentury integration with a coupled ocean–atmosphere general circulation model and involves interactions of the thermohaline circulation with the atmosphere in the North Atlantic and interactions between the ocean and the atmosphere in the North Pacific. The authors focus on the physics of the North Atlantic interdecadal variability. If, for instance, the North Atlantic thermohaline circulation is anomalously strong, the ocean is covered by positive sea surface temperature (SST) anomalies. The atmospheric response to these SST anomalies involves a strengthened North Atlantic Oscillation, which leads to anomalously weak evaporation and Ekman transport off Newfoundland and in the Greenland Sea, and the generation of negative sea surface salinity (SSS) anomalies. These SSS anomalies weaken the deep convection in the oceanic sinking regions and subsequently the strength of the thermohaline circulation. This leads to a reduced poleward heat transport and the formation of negative SST anomalies, which completes the phase reversal. The Atlantic and Pacific Oceans seem to be coupled via an atmospheric teleconnection pattern and the interdecadal Northern Hemispheric climate mode is interpreted as an inherently coupled air–sea mode. Furthermore, the origin of the Northern Hemispheric warming observed recently is investigated. The observed temperatures are compared to a characteristic warming pattern derived from a greenhouse warming simulation with the authors’ coupled general circulation model and also with the Northern Hemispheric temperature pattern associated with the 35-yr climate mode. It is shown that the recent Northern Hemispheric warming projects well onto the temperature pattern of the interdecadal mode under consideration.